Maximizing athletic performance in the heat - Pryor, R. R.; Casa, D. J; Adams, W. M.; Belval, L. N.; DeMartini, J. K.; Huggins, R. A.; Stearns, R. L.; Vandermark, L. W. (Strength and Conditioning Journal, 2013)
Athletes train and perform at optimal levels in cool environments; however, many individuals do not alter their training in hot environments. The purpose of this review is to explore existing research related to enhancing performance in the heat by modifying the following practices: (a) hydration, (b) body cooling, (c) heat acclimatization, (d) clothing and protective equipment, (e) nutrition and supplementation, (f) sleep, and (g) technology. This review explores practical ways athletes can change their exercise habits with the goal of increasing performance in hot environments.